Membincang Praktik Asuransi di Indonesia Telaah Sosiologi Hukum - Khusniati Rofi'ah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2013)
In this modern era, the discussion of Islamic law issues is more on muamalah issues than worship. Issues related to the economy, including insurance institutions. As a result of the globalization process, this insurance institution was brought to the Islamic world. So, it is the duty of Islamic law to follow up or give a response, both in the form of formal legality.response, either in the form of formal legality or in the form of Islamicizing the institution. This insurance issue is not explicitly explained in the text. Therefore, the problem of insurance is seen as a matter of ijtiha>di> that is, a matter of difference of opinion. The practice of insurance in the culture of Indonesian society on a non-formal basis has actually been done frequently. As for institutionalized insurance, there has not been much response. Insurance actually has many broad and complex benefits, in addition to providing a symbiotic mutualism between customers.symbiotic mutualism between customers and companies. However, the Indonesian people still do not utilize the existence of insurance companies as a means of protecting themselves and their families and property from unexpected events. The public is still very unfamiliar with insurance and not much familiar with the types of insurance production available. Seeing the benefits of such insurance, Islamic law as an elaboration and actual application of shari'ah must be translated by following the spirit of the times and humanity, so that its inner-dynamic as a law for humans will not lose its context.